Identification of a Novel Heart–Liver Axis: Matrix Metalloproteinase‐2 Negatively Regulates Cardiac Secreted Phospholipase A2 to Modulate Lipid Metabolism and Inflammation in the Liver. Issue 11 (November 2015) - Hernandez‐Anzaldo, Samuel; Berry, Evan; Brglez, Vesna; Leung, Dickson; Yun, Tae Jin; Lee, Jun Seong; Filep, Janos G.; Kassiri, Zamaneh; Cheong, Cheolho; Lambeau, Gérard; Lehner, Richard; Fernandez‐Patron, Carlos
Abstract : Background: Endocrine functions of the heart have been well established. We investigated the hypothesis that cardiac secretion of a unique phospholipase A2 recently identified by our laboratory (cardiac secreted phospholipase A2 [sPLA2 ]) establishes a heart–liver endocrine axis that is negatively regulated by matrix metalloproteinase‐2 (MMP‐2). Methods and Results: In Mmp2 −/− mice, cardiac (but not hepatic) sPLA2 was elevated, leading to hepatic inflammation, immune cell infiltration, dysregulation of the sterol regulatory element binding protein‐2 and liver X receptor‐α pathways, abnormal transcriptional responses to dietary cholesterol, and elevated triglycerides in very low‐density lipoprotein and in the liver. Expression of monocyte chemoattractant protein‐3, a known MMP‐2 substrate, was elevated at both mRNA and protein levels in the heart. Functional studies including in vivo antibody neutralization identified cardiac monocyte chemoattractant protein 3 as a possible agonist of cardiac sPLA2 secretion. Conversely, systemic sPLA2 inhibition almost fully normalized the cardiohepatic phenotype without affecting monocyte chemoattractant protein‐3. Finally, wild‐type mice that received high‐performance liquid chromatography–isolated cardiac sPLA2 from Mmp2 −/− donors developed a cardiohepatic gene expression profile similar to that of Mmp2 −/− mice. Conclusions: These findings identified the novel MMP‐2/cardiac sPLA2 pathway that endows the heart with important endocrine functions, including regulation of inflammation and lipid metabolism in the liver. Our findings could also help explain how MMP2 deficiency leads to cardiac problems, inflammation, and metabolic dysregulation in patients.